2003
DOI: 10.1080/0003684022000025440
|View full text |Cite
|
Sign up to set email alerts
|

Budget deficits, money growth and inflation: the Turkish evidence

Abstract: The paper investigates the long-run relationships between budget deficits, inflation and monetary growth in Turkey considering two alternative trivariate systems corresponding to the narrowest and the broadest monetary aggregates. While the joint endogeneity of money and inflation rejects the validity of the monetarist view, lack of a direct relationship between inflation and budget deficits makes the pure fiscal theory explanations illegitimate for the Turkish case. Consistent with the policy regime of financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…Simimi (2000) and Simimi and jamshidbaygi (2011) focusing on relationship for Iranian economy strongly confirmed positive relationship between budget deficits and inflation. Metin (1998Metin ( ), Özatay (2000, Seljuk (2001), Tekin-Koru and Özmen (2003) and Kia (2010) provided the empirical evidence from Turkish economy that deficits and government debt remained important factors behind inflation during different time spans. Evidence from African countries was established by Onwioduokuokit (1999) and Chimobi and Igwe (2010).…”
Section: Empirical Studiesmentioning
confidence: 97%
“…Simimi (2000) and Simimi and jamshidbaygi (2011) focusing on relationship for Iranian economy strongly confirmed positive relationship between budget deficits and inflation. Metin (1998Metin ( ), Özatay (2000, Seljuk (2001), Tekin-Koru and Özmen (2003) and Kia (2010) provided the empirical evidence from Turkish economy that deficits and government debt remained important factors behind inflation during different time spans. Evidence from African countries was established by Onwioduokuokit (1999) and Chimobi and Igwe (2010).…”
Section: Empirical Studiesmentioning
confidence: 97%
“…The debate regarding the causal outcome due to the inter‐relationship amongst budget deficits, the growth of money supply and the price level is still controversial due mainly to conflicting results obtained by previous empirical studies. While Tekin‐Koru and Ozmen () for Turkey support the Sargent and Wallace Hypothesis, Ozatay (), Ozmen and Kogar () and Ozatay () all for Turkey reason along the fiscal theory of the price level. Also, Woodford () supports the fiscal theory of the price level (FTPL).…”
Section: Context and Justificationmentioning
confidence: 97%
“…The FTPL model posits that causality runs from government budget deficit to change in price level and then from change in price level to money growth. The FTPL does not deny the possibility that fiscal disturbances may affect money supply (Tekin‐Koru and Ozmen, ). This framework suggests the neutrality of money in influencing inflation in a non‐Ricardian environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The result also confirmed the findings of Fisher, Sahay and Vegh (2002) which reported that fiscal deficits derived inflation in developing economies. Furthermore, this was not at variant with Tekin-Koru and Ozmen (2003) who found that prices were not determined by monetary growth, but only adjust to the increase in the private sector nominal wealth caused by the deficits that were financed with bonds. The impulse response functions revealed that inflation responded to one standard deviation shocks in total debts in more conspicuous manner than in monetary base, which showed that total government debts financing explained variability in inflation in Nigeria better than monetary base.…”
Section: Cointegrationmentioning
confidence: 87%